Deuḍā: A Resonance of Folk Poetic Tradition (Far Western Review, 2025)
This study explores the folk poetic ambiance of Ḍeuḍā, an oral art form deeply embedded in the cultural fabric of Sudurpaschim Province, Nepal. Grounded in the theoretical perspectives of orality and folklore studies, the research examines the poetic qualities, cultural significance, and communal essence of Ḍeuḍā songs. Using qualitative methodologies, including textual analysis, field observations, and interviews, the study highlights how Ḍeuḍā encapsulates the emotions, experiences, and traditions of people. Characterized by simplicity, spontaneity, and a profound connection to communal life, Deuḍā songs are rich in lyricality, rhythm, and emotional depth, reflecting the joys and struggles of everyday existence. These songs, composed and performed orally in dialogic or collective settings, address themes such as love, nature, social justice, and political commentary. Their oral transmission preserves historical memory while allowing for variation and adaptation, making each performance a unique cultural expression. The findings emphasize Ḍeuḍā as a living folk poetic tradition that bridges the past and present, retaining its authenticity through its deep roots in the lives of ordinary people. The collective emotions of performers and audiences shape its ambiance, fostering empathy and cultural solidarity. However, the study also identifies challenges to its continuity, including the impact of modernization and the decline of oral traditions. By situating Ḍeuḍā within the broader framework of folk poetic traditions, the research celebrates its role as a dynamic repository of cultural heritage and a medium of communal expression. The study advocates for sustained efforts to preserve and promote Deuḍā, ensuring that its rich folk poetic tradition endures for future generations.